Recruitment And Selection Procedures For Non-Executive Employees PT Nusantara Medika Utama: Prosedur Rekrutmen Dan Seleksi Pekerja Non-Calon Pimpinan PT Nusantara Medika Utama - Salsabila Diar Kirani; Sulastri Irbayuni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
In achieving the vision and mission of an organization, human resources are needed who have the capacity and quality that are in accordance with the needs. PT. Nusantara Medika Utama is one of the health facility management companies in Central Java and East Java which includes several hospital facilities, treatment clinics, ERs, and aesthetics. This activity focuses on the recruitment and selection procedures for non-leadership candidates at PT Nusantara Medika Utama. The implementation of the activity aims to evaluate practical steps in the recruitment and selection process for workers for the non-leadership candidate category. The impact of the implementation of the activity is expected to maximize the acquisition of human resources that are in accordance with the company's needs. Based on the results of the implementation of this activity, it can be seen that the procedures carried out by PT. Nusantara Medita Utama in recruiting new workers consist of several stages. The first stage is Pre-Recruitment in the form of identifying worker needs, the process of accepting applications and administrative selection, Academic Potential Tests, Psychological Tests, Interviews and Health Tests, to signing work contracts. Several suggestions have been submitted to improve the efficiency and effectiveness of the implementation of the recruitment process.